(untitled) (International Journal of Current Engineering and Technology, 2015)
Gears are known for effective transferring of power from one shaft to another by maintaining a definite velocity ratio. Classical method AGMA (American Gear Manufacturing Association) standards are followed to design gears to ascertain the constant transmission of torque and angular speeds of shafts. In reality torque, rotational speed, gear material properties, shaft-alignment and gear geometry are statistical in nature. To account such variability in operating and geometric conditions, the AGMA standards recommend usage of a large number of empirical design factors. Due to subjective nature of those factors, often wrong input design factors lead to over-design or under-design of the gear. To decide the appropriate values of correction factors, it is advisable to account statistical variations in operating and geometric conditions in the form of their mean and standard deviation values. In the present work, a methodology of probabilistic design for durability of spur gear has been presented accounting pitting failure. A case study has been considered to compare the procedure suggested by AGMA standard and the proposed methodology.